2015
DOI: 10.3847/0004-637x/816/1/2
|View full text |Cite
|
Sign up to set email alerts
|

The Parker Instability in Disk Galaxies

Abstract: We examine the evolution of the Parker instability in galactic disks using 3D numerical simulations. We consider a local Cartesian box section of a galactic disk, where gas, magnetic fields, and cosmic rays are all initially in a magnetohydrostatic equilibrium. This is done for different choices of initial cosmic-ray density and magnetic field. The growth rates and characteristic scales obtained from the models, as well as their dependences on the density of cosmic rays and magnetic fields, are in broad agreem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…This equipartition could be the result of a self-regulated feedback process: provided that CR and magnetic midplane pressures are supercritical, their buoyancy force overcomes the magnetic tension of the dominant toroidal magnetic field, causing it to bend and open up (Parker 1966;Rodrigues et al 2016). CRs stream and diffuse ahead of the gas into the halo along these open field lines and build E-mail: tthomas@aip.de (TT), cpfrommer@aip.de (CP) up a pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…This equipartition could be the result of a self-regulated feedback process: provided that CR and magnetic midplane pressures are supercritical, their buoyancy force overcomes the magnetic tension of the dominant toroidal magnetic field, causing it to bend and open up (Parker 1966;Rodrigues et al 2016). CRs stream and diffuse ahead of the gas into the halo along these open field lines and build E-mail: tthomas@aip.de (TT), cpfrommer@aip.de (CP) up a pressure gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Polarized radio observations of edge-on galaxies show poloidal field lines at the disk-halo interface (e.g., Tüllmann et al 2000). This argues for a dynamical mechanism that is responsible for reorienting the toroidal magnetic field in the disk and may be explained by a CR-driven Parker instability (Rodrigues et al 2016). Indeed, recent hydrodynamical simulations of the formation and evolution of disk galaxies have shown that CR pressure can drive strong bipolar outflows in disk galaxies provided they are allowed to stream (Uhlig et al 2012;Ruszkowski et al 2016) or diffuse (Booth et al 2013; relative to the rest frame of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…Our stability analysis is a variant of the magnetic buoyancy instability in which magnetic field lines and the direction of the perturbations are in parallel. Importance of the magnetic buoyancy instability in the Galactic disc (including cosmic ray component) to explain formation of the molecular clouds has been emphasized by Parker (1966) and further developments towards understanding nonlinear evolution of this instability are based on the direct numerical simulations (e.g., Matsumoto et al 1993;Basu et al 1997;Hanasz & Lesch 2003;Rodrigues et al 2016). However, we did not explore magnetic buoyancy instability in the presence of a radiation field when the perturbations are perpendicular to the magnetic field vector.…”
Section: Astrophysical Implications: Radiative Bubbles In the Massivementioning
confidence: 99%